Solidarity collaboration networks: two case studies in the stateof Hidalgo, Mexico - Percastegui Gutiérrez, Adnai Yoana (Cooperativismo & Desarrollo, 2023)
The deployment of the Solidarity Economy (se) in Mexico has been relative due to the political, cultural, economic, and social context of the country. There are diverse experiences that emerge from it and that remain firm in their task of building and demonstrating that another world is possible, placing the reproduction of life and not capital, as the guiding axis of their actions. Adding to the construction of an alternative paradigm to the dominant one, it is necessary to make visible, contribute and deepen these practices, to this end, this article exposes the experiences of two Solidarity Collaboration Networks in the state of Hidalgo; result of a qualitative study using the participatory action research methodology in Magueyal Subject and Community A.C., and the Autonomous and Free Hidalgo Community with Solidarity Economies. It shows how these networks are coping with instrumental rationality, through the reordering of representations and actions in the search for new learning capable of placing the reproduction of life at the center.
Keywords: collaboration networks; construction of commons; reproduction of life; Hidalgo; Mexico; solidarity economy